1997
DOI: 10.1111/j.1744-7348.1997.tb05778.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on population dynamics and spatial distribution of leafhoppers in vineyards (Homoptera: Cicadellidae)

Abstract: Thirty-two species of Cicadellidae, including the Macropsinae, Agalliinae, Penthimiinae, Aphrodinae, Cicadellinae, Typhlocybinae and Deltocephalinae, 10 of which were already known as phytoplasma vectors, were captured in vineyards using yellow sticky traps. Adult population dynamics of the most abundant species of Penthimiinae and Deltocephalinae were studied over the whole growing season. Penthimia nigra was captured in May and June, Anoplotettix fuscovenosus in June-August, Fieberiella jlorii in August-Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 14 publications
4
32
0
Order By: Relevance
“…By using an artiÞcial feeding-medium technique, N. fenestratus has also been shown to be positive for stolbur phytoplasma (Orenstein et al 2003) and to transmit aster yellow (Landi et al 2013). The main known host plants for N. fenestratus are various species of Asteraceae: Tussilago farfara L. (coltsfoot; Bosco et al 1997), Leontodon sp. (hawkbits), Helichrysum sp.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…By using an artiÞcial feeding-medium technique, N. fenestratus has also been shown to be positive for stolbur phytoplasma (Orenstein et al 2003) and to transmit aster yellow (Landi et al 2013). The main known host plants for N. fenestratus are various species of Asteraceae: Tussilago farfara L. (coltsfoot; Bosco et al 1997), Leontodon sp. (hawkbits), Helichrysum sp.…”
mentioning
confidence: 97%
“…Moreover, the females of the leafhopper Macrosteles quadrilineatus Forbes transmit aster yellow phytoplasma at a higher frequency than the males do, and their migrant populations generally consist primarily of females (Weintraub and Beanland 2006). However, males are known to have high dispersal ability in many leafhopper and planthopper species, whereas females tend to remain sedentary on their host plant (Denno and Roderick 1990, Bosco et al 1997, Hoy et al 1999. Finding and choosing a good site for oviposition within the plant community is a demanding task for the females, and they can be inßuenced by a variety of factors (e.g., host-plant availability, mortality risks for mother, and larvae that affect reproductive success; Hilker and Meiners 2002).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Some information on spatial distribution (Bosco et al 1997), population dynamics (Bernard and Du Fretay 1988), and seasonal adult occurrence (Lessio et al 2003) is available, but other aspects of its behavior such as daily ßight activity and inßuence of temperature and relative humidity on movement behavior were never investigated. Studies of daily movement are known for other vectors such as Frankliniella occidentalis (Pergande) (Pearsall 2002), Circulifer hematoceps (Mulsant et Rey) (Kersting and Baspinar 1995), Paraphlesius irroratus (Say) (Larsen and Whalon 1987), Bemisia tabaci (Gennadius) (Blackmer and Byrne 1993), and aphids (Wiktelius 1981).…”
mentioning
confidence: 99%
“…Biodiversity studies conducted in two commercial vineyards in QC from 1997 to 1999 found 59 leafhopper species associated with vineyards (Bostanian et al 2003). Worldwide, there have been few studies on biodiversity, distribution, and abundance of leafhoppers in vineyards (Bonfils and Schvester 1960;Bosco et al 1997;Boukhris-Bouhachem et al 2007;Dér et al 2009). Descriptions of leafhopper species associated with vineyards are frequently part of studies on the arthropod fauna of vineyards (e.g., Bostanian et al 2003;Böll and Herrmann 2004;Altieri et al 2005;De Valpine et al 2010).…”
Section: Introductionmentioning
confidence: 99%